2009
DOI: 10.1186/1746-160x-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Histological evaluation of the influence of magnetic field application in autogenous bone grafts in rats

Abstract: BackgroundBone grafts are widely used in oral and maxillofacial reconstruction. The influence of electromagnetic fields and magnets on the endogenous stimulation of target tissues has been investigated. This work aimed to assess the quality of bone healing in surgical cavities filled with autogenous bone grafts, under the influence of a permanent magnetic field produced by in vivo buried devices.MethodsMetal devices consisting of commercially pure martensitic stainless steel washers and titanium screws were em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…SMF has been studied as a noninvasive physical treatment for promoting bone growth and bone healing, and preventing bone loss (Zhang et al, 2014a). Animal studies have revealed that certain SMFs have a synergistic role in such circumstances as bone surgical invasion (~50 mT) (Yan et al, 1998), ischemic bones (~50 mT) (Xu et al, 2001), ovariectomized rats (180 mT) (Xu et al, 2011), adjuvant arthritis rats (30-80 mT) (Taniguchi et al, 2004), bone fracture (4 mT) (Puricelli et al, 2006) and bone grafts (4 mT) (Puricelli et al, 2009). Most cellular studies indicate that the anabolic effects on bone homeostasis are due to the enhanced activities of osteoblast and promoted osteogenic differentiation in mesenchymal stem cells, although the underlying mechanisms of SMF effects on cell activities are still unclear (Colbert et al, 2009;Markov, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…SMF has been studied as a noninvasive physical treatment for promoting bone growth and bone healing, and preventing bone loss (Zhang et al, 2014a). Animal studies have revealed that certain SMFs have a synergistic role in such circumstances as bone surgical invasion (~50 mT) (Yan et al, 1998), ischemic bones (~50 mT) (Xu et al, 2001), ovariectomized rats (180 mT) (Xu et al, 2011), adjuvant arthritis rats (30-80 mT) (Taniguchi et al, 2004), bone fracture (4 mT) (Puricelli et al, 2006) and bone grafts (4 mT) (Puricelli et al, 2009). Most cellular studies indicate that the anabolic effects on bone homeostasis are due to the enhanced activities of osteoblast and promoted osteogenic differentiation in mesenchymal stem cells, although the underlying mechanisms of SMF effects on cell activities are still unclear (Colbert et al, 2009;Markov, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…It has also been shown in vitro and in vivo , that biophysical stimulation via the application of electric currents enhances bone healing and restores structural strength ( 13 – 15 ). Based on these findings, electrical bone growth stimulators have been developed for clinical application ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…For many years, EMFs have been researched as a stimulation method to enhance bone regeneration in maxillofacial surgery, including dental implants, distraction osteogenesis, and bone grafts. 21 , 38 , 39 The knowledge from recent studies 40 , 41 has conclusively demonstrated that the contribution of EMFs to the bone healing process is based on stimulating the expression of growth factors, such as vascular endothelial growth factor and bone morphogenetic protein. EMFs also induce angiogenesis, migration, proliferation, and differentiation of stem cells from the surrounding mesenchymal tissues into cartilage and bone-forming cells in an area of injury.…”
Section: Discussionmentioning
confidence: 99%